Application of porous titanium acetabular cup at hip arthroplasty in case of acetabulum wall defects - Filipenko, Volodymyr; Bondarenko, Stanislav; Denisenko, Sergey; Badnaoui, Ahmed (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Total hip arthroplasty (THA) at acetabulum defects is an actual problem of modern orthopaedics, as it is associated with multiple complications. Objective: to evaluate the results of porous titanium cups application in patients with acetabulum defects of various etiologies. Material and methods: there were 83 patients (98 hip joints) in the period from 2016 to 2019 with acetabulum walls defects who underwent cementless THA with the use of porous titanium acetabular cups with «pressfit» fixation with Trabecular Titanium Metal (pores sized from 600 to 800 microns, porosity 80 %, elastic modulus 12.9 GPa, friction coefficient 1.08). The average age of the patients was 55.7 years (34 to 80 years); 28 men and 55 women. The average body mass index was 28.6. The assessment of acetabulum defects was carried out according to D’Antonio classification. In all cases, lateral approach to the hip joint was used, acetabular components were implanted in the anatomical position with the restoration of hip rotation center. In 9 cases the reconstruction of acetabulum defects was performed with structural autografts, in 87 — spongy autografts, in 2 — a combination of these two grafting methods. Results: the average follow-up for patients was 23 months. The functional state of the hip joint according to Harris Hip Score increased from an average of 37 to 89 points. During the post-operative follow-up, radiological signs of the components’ instability were not detected. All patients showed a complete incorporation of autografts after surgery. Conclusion. The use of porous titanium acetabular cups «press-fit» fixation in THA of patients with defects of acetabulum walls gives the possibility to obtain positive clinical outcome of surgical treatment in the early post-operation period.